Essays on the Quality of Life - Michalos, Alex C. author. aut Link
XII, 492 p.
Keywords: Since initiating the journal Social Indicators Research in 1974, Alex C. Michalos has been a pioneer in social indicators and quality-of-life research. This collection of nineteen articles provides an overview of nearly 30 years of work, including papers drawn from diverse sources and papers never published before. Topics range over quality of life investigations connected to the problems of combining social, economic and environmental indicators, measuring the status of women in Canada, housing and migration, health and human well-being, older peoples' well-being, leisure activities and health, impact of public services, police services, criminal victimization, feminism and ethnic relations on the quality of life. The final paper, on multiple discrepancies theory (MDT), is the author's unique contribution to an empirically testable new foundation for theories of utility, satisfaction and happiness.